Здобуття незалежності у суспільній свідомості громадян України - Шульга, Т.С. (Український історичний журнал, 2011)
Розглянуто часову (на відтинку 1999–2010 рр.) й регіональну динаміку, а також відмінності між віковими групами населення у ставленні громадян нашої країни до здобуття незалежності. Зроблено спробу визначити основні
чинники еволюції підтримки самостійності України як одного з проявів лояльності до держави. The article is devoted to attitudes of Ukraine’s citizenry towards the nation’s
achievement of independence (1991). The author describes regional and generational
differences, as well as dynamics of this phenomenon’s development through the
period in question (1999 to 2010). This study attempts to establish main reasons
behind evolution of support for the country’s independent statehood, with this
support seen as a manifestation of loyalty to the state, whatever its origin.